PENDIDIKAN KARAKTER DALAM MASYARAKAT BUGIS - Ismail Suwardi Wekke, Arhanuddin Salim, Yunus Salik (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2018)
This study aims to portray the character education contained in the Bugis community that many people do not know about it. For the Bugis community, local knowledge is not just a mere habit, but customs is a prerequisite for human life. Then there is the phrase saying if tampered domestic customs of the wine stops dripping, fish disappeared too, and the rice was not going to be ‘so Boogies retaining local knowledge as a foundation/ backrest one is the first, Siri (shame)means: Shyness (self-esteem), used to defend the honor of the people who want to trample on his self-esteem. The shame is closely connected with: (a) honor (honor), (2) self-esteem (high respect), (3) the dignity of (value), (4) dignity (dignity) as a human being. While the second, sipakatau, sipakainge and sipakalebbi (3S) have an impact on the realization of the conception of basic values, namely the formation of values such as: (1) the value of the determination, the motivation and outlook on life; (2) the value of courage, emotional temperament a value in maintaining self-esteem, (3) the value of solidarity, which is the value of mutual cooperation, (4) the value of courtesy language, proficiency in accordance Bugis ethnic culture (socio-psycholinguistic repertoire). Intangible: (1) Mali’u sipakainge “ if wrong, to remind each other, (2) sipakatau or sipakalebbi “mutual respect or mutual glorify”, (3) sibaliperri’ ‘mutual aid’, (4) sisaro mase ‘mutual love, (5) Tudang Sipulung ‘sit together’ culture-conference failed. Therefore local knowledge is very important and is expected to be the glue for the creation of harmony.Keywords: Konsep Sirri, 3S, Masayarakat Bugis